LRG1 and SDR16C5 protein expressions differ according to HPV status in oropharyngeal squamous cell carcinoma - Randén-Brady, Reija; Carpén, Timo; Hautala, Laura C.; Tolvanen, Tuomas; Haglund, Caj; Joenväärä, Sakari; Mattila, Petri; Mäkitie, Antti; Lehtonen, Sanna; Hagström, Jaana; Silén, Suvi (Springer Nature, 2025)
The increasing incidence of oropharyngeal squamous cell carcinoma (OPSCC) is primarily due to human papillomavirus, and understanding the tumor biology caused by the virus is crucial. Our goal was to investigate the proteins present in the serum of patients with OPSCC, which were not previously studied in OPSCC tissue. We examined the difference in expression of these proteins between HPV-positive and -negative tumors and their correlation with clinicopathological parameters and patient survival. The study included 157 formalin-fixed, paraffin-embedded tissue samples and clinicopathological data. Based on the protein levels in the sera of OPSCC patients, we selected 12 proteins and studied their expression in HPV-negative and HPV-positive OPSCC cell lines. LRG1, SDR16C5, PIP4K2C and MVD proteins were selected for immunohistochemical analysis in HPV-positive and -negative OPSCC tissue samples. These protein´s expression levels were compared with clinicopathological parameters and patient survival to investigate their clinical relevance. LRG1 expression was strong in HPV-negative whereas SDR16C5 expression was strong in HPV-positive tumors. Correlation was observed between LRG1, SDR16C5, and PIP4K2C expression and patient survival. High expression of PIP4K2C was found to be an independent prognostic factor for overall survival and expression correlated with HPV-positive tumor status. The data suggest the possible role of LRG1, SDR16C5 and PIP4K2C in OPSCC biology.